Studies on some aspects of the fishery of Oreochromis mossambicus in Maduru oya reservoir - De Silva, S. (My University, 1985)
This dissertation is tl~ result of a study cBrti~d out during a seven month period ~rom Janwiry to July 1985, in tl~ Maduru Oya Reservoir. 'rho fibbing is done by 5.6 m fibre glass "Kulla" boats fl.1d is' exclusively a gill net fishery. There is ono landing sita lor toe reservoir and the estimated Jandirii::S at tbe site du.r1.ng the seven month poriad. is three hundred MT. An average of 96 craft per month had been in operation and about 150 fislJermenwere engaged in the fishery. The growtn para~eters for the ~ajor species Oreochromis rnoBsambicus we:r.'e as tjnn, tedr;o be IJ '" 35.5 ems i and CP -. K (annual) =2.Q62. The instantaneous nutural mortality was estimated at 2.736. 'l'r e length we:i t rolart 1011Ghip was estimated to be~; '" 0.1374 L2. .3999" The potential fish yield was estimatedto be 953 MT. per annum. The exploitation rate \V'HiI~()1;,~:'C'r"ined to be . .26 which1ndicates that there is room for expansion of thefisflery.